2021
DOI: 10.3390/ijms22169051
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Arming Factors—The Current Paradigm for Oncolytic Vectors Relies on Immune Stimulating Molecules

Abstract: The dogma of engineering oncolytic viral vectors has shifted from emphasizing the viral lysis of individual cancer cells to the recruitment and coordination of the adaptive immune system to clear the tumor. To accomplish this, researchers have been adding several classes of transgenes to their preferred viral platforms. The most prevalent of these include antibodies and targeting moieties, interleukins and cytokines, and genes which rely on small molecule co-administration for tumor killing. Most current vecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…While unmodified oncolytic viruses often display efficacy in preclinical models, a significant body of literature has shown that this efficacy can be dramatically improved by genetic “arming” of the viral backbone. 36 It is therefore not surprising that several studies have examined the potential of improving OVT as a NAT by using recombinant, armed viruses. Indeed, the first published work investigating the use of OVT as a NAT used an HSV armed with interleukin 12 (IL-12).…”
Section: Efficacy Of Ovt As a Neoadjuvant Therapy In Preclinical Modelsmentioning
confidence: 99%
“…While unmodified oncolytic viruses often display efficacy in preclinical models, a significant body of literature has shown that this efficacy can be dramatically improved by genetic “arming” of the viral backbone. 36 It is therefore not surprising that several studies have examined the potential of improving OVT as a NAT by using recombinant, armed viruses. Indeed, the first published work investigating the use of OVT as a NAT used an HSV armed with interleukin 12 (IL-12).…”
Section: Efficacy Of Ovt As a Neoadjuvant Therapy In Preclinical Modelsmentioning
confidence: 99%